Manfaat Perpustakaan Keliling Kantor Arsip, Perpustakaan dan Dokumentasi Kota Padang Bagi Siswa SD Negeri 23 Ampalu Pengambiran Kota Padang - Almi, Aulia; Nst., Bakhtaruddin (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This study aimed to: (1) describe how the bookmobile operations in the Office of Library Archives and Documentation Padang, (2) describe what benefits students in elementary school to 23 Ampalu Pengambiran city of Padang with the bookmobile in the Archives Library and Documentation Padang. Data were collected through observation and interviews with user and Librarians Library Archives and Documentation Office of the city of Padang. Analyzing the data be descriptive. By analyzing the data concluded: some benefits of mobile library services for pemustaka well as one means of promotion are as follows: (1) foster interest in reading in the middle of the community, (2) the bookmobile pemustaka easier to get the information needed (3) pemustaka away from public libraries can enjoy the library with the library, (4) the government can still understand the importance of education in the community (users) and be aware of the high interest in reading among children Indonesia. Keywords: bookmobile; library services